Sektor Parawisata di Manca Negara: Analisis Daya Saing Komparatif Indonesia dan Negara ASEAN: Tourism Sector Abroad: Comparative Competitiveness Analysis of Indonesia and ASEAN Countries - Gea, Imelda Veronica; Hotsawadi, Hotsawadi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2025)
Indonesia has a wealth of natural resources and cultural diversity that can be developed to boost the performance of Indonesia's tourism exports in the global market. However, it has been identified that the Indonesian tourism sector is still less competitive than other ASEAN countries, especially Thailand and Singapore, in the global market. For this reason, this research aims to investigate and identify the competitiveness of the Indonesian tourism sector in the global market compared to other ASEAN countries using the Revealed Comparetive Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Market Share Index (MSI) analysis methods and panel data regression. The results of the analysis found that the sector performance and competitiveness of Thailand's tourism sector was higher than Indonesia's. On the other hand, the results of the analysis of the market share position of the Indonesian tourism sector for the twenty main targets are only around 17,398 percent with an average of 0.870 percent from 2019 to 2021. This condition shows that the potential of Indonesia's natural tourism sector with its large wealth of natural and cultural resources has not been utilized optimally to attract tourists to visit Indonesia. From the perspective of panel data regression analysis, it was identified that the variables of trade openness, population level of partner countries, real GDP of partner countries, real exchange rate (Rp/LCU) and competitiveness had a positive and significant effect on the performance of the Indonesian tourism sector. For this reason, government strategies and policies are needed to support strengthening competitive performance through strengthening infrastructure, improving the quality of human resources, creating a supportive investment climate and promoting integrated and targeted tourism.